2018
DOI: 10.1111/anu.12856
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of fish and rapeseed oils on growth performance, egg fatty acid composition and offspring quality of sterlet sturgeon (Acipenser ruthenus)

Abstract: The aim of this study was to evaluate the long‐term effects (7‐month experiment) of diets consisting of fish oil (Kilka fish) and vegetable oil (rapeseed) on the reproductive performance of sterlet sturgeon (Acipenser ruthenus) broodstock. Forty‐five broodstock (990.3 ± 20.05 g) were randomly allocated to three different diet treatments. Three experimental diets were formulated with graded levels of fish oil (100% FO), vegetable oil (100% VO), and a combination of fish and vegetable oil (50% FO + 50% VO). At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The remaining constant ARA levels in the carcass from fish fed different oil content in all experimental dietary treatments underline the possibility of the selective uptake and retention of ARA and its value for the metabolism and developing Caspian brown trout fingerlings. The previous findings on the importance and function of ARA for egg and larvae development and its selectively incorporate in various species of fish support this idea (Masoudi Asil et al, 2017; Pourhosein‐Sarameh, Bahri, Falahatkar, et al, 2019; Pourhosein‐Sarameh, Bahri, Salarzadeh, et al, 2019). Moreover, in our study, given that the highest and lowest n‐3/n‐6 ratios were observed in fingerlings fed HF and HV, respectively.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The remaining constant ARA levels in the carcass from fish fed different oil content in all experimental dietary treatments underline the possibility of the selective uptake and retention of ARA and its value for the metabolism and developing Caspian brown trout fingerlings. The previous findings on the importance and function of ARA for egg and larvae development and its selectively incorporate in various species of fish support this idea (Masoudi Asil et al, 2017; Pourhosein‐Sarameh, Bahri, Falahatkar, et al, 2019; Pourhosein‐Sarameh, Bahri, Salarzadeh, et al, 2019). Moreover, in our study, given that the highest and lowest n‐3/n‐6 ratios were observed in fingerlings fed HF and HV, respectively.…”
Section: Discussionmentioning
confidence: 74%
“…One more considerable observation from our study was that the fingerlings fed 100% FO diet had the lowest protein efficiency than fingerlings fed HV, FV, and FF diets. It is documented that a diet containing various FA profiles can induce various effects on aspects of fish lipid metabolism such as FA digestibility, depositional and/or absorption processes, catabolism, FA uptake and transport, and so on (Pourhosein‐Sarameh, Bahri, Falahatkar, et al, 2019; Pourhosein‐Sarameh, Bahri, Salarzadeh, et al, 2019; Turchini et al, 2009). Besides, the inordinate amounts of lipid in diet could exert a diminution in the absorption efficiency of nutrition components or digestive enzyme activities (Zhao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7.0, Molecular Biology Insights Inc., Colorado, USA; Table 2). Further, the β-actin was used as an ideal housekeeping gene to normalize the gene expression levels of the selected genes based on its constant expression levels in A. ruthenus (Pourhosein Sarameh et al, 2019). The relative expression of the selected genes was measured with an iCycler iQ real-time PCR (Bio-Rad) using the WizPure qPCR master mix (Wizbio Solutions) as SYBR green fluorescent dye and gene-specific primers.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Fish oil is an excellent lipid source for broodstock of fishes, including pearl gourami ( Trichogaster leeri ) [ 6 ] and gilthead seabream ( Sparus aurata ) [ 7 ], because of its high LC-PUFA content. Studies have shown that partial replacement of FO with OO or RO can promote the reproductive performance of tongue sole ( Cynoglossus semilaevis ) [ 8 ], Atlantic salmon ( Salmo salar ) [ 9 ], and sterlet sturgeon ( Acipenser ruthenus ) [ 10 ], although excessive replacement of FO was reported to decrease the reproductive performance of sterlet sturgeon [ 10 ]. However, little is known about the effects of dietary OO on the gonad development and reproduction of tilapia.…”
Section: Introductionmentioning
confidence: 99%